Conservação do Jaborandi (Pilocarpus microphyllusStapf Ex Wardleworth) no Norte do Brasil: diversidade genética e impactos das mudanças climáticas futuras - CORRÊA, Waléria Pereira Monteiro (Universidade Federal do Pará, 2025)
Jaborandi (Pilocarpus microphyllus Stapf Ex Wardleworth) is a medicinal plant found in the north/northeast of Brazil. In recent decades, disordered extractive exploitation, the advance of agriculture and other activities that result in deforestation, as well as ongoing climate changes, have induced direct and indirect impacts on the survival of this plant species. Jaborandi is a natural source of pilocarpine, an alkaloid used in the pharmaceutical industry to treat glaucoma and xerostomia. Therefore, the species is socio-environmental interest because the extractivism of its leaves has generated financial income for countless families, in addition to contributing to the conservation of the species in the region. In order to contribute to long-term conservation and survival strategies for the species, this study evaluated the structure and genetic diversity of the species P. microphyllus in a Conservation Unit (UC) in southeastern Pará (FLONA Carajás), as well as an environmental modeling study was developed to analyze the impacts of climate change on the geographic distribution of occurrence of jaborandi, in order to delineate suitable areas according to future climate scenarios. The results of the genetic study demonstrated the formation of 04 populations with high diversity and ecological structure, even with continuous extractivism within the Carajás FLONA, indicating that exploration has been taking place in a sustainable manner in the region. In the modeling study, the projections indicated impacts of climate change on the distribution of P. microphyllus with a reduction in suitable areas in the Cerrado and Caatinga biomes (Maranhão and Piauí) and expansion of the species in the protected areas of forest cover of the Amazon biome in southeastern Pará. The results of this study contribute to the understanding of diversity in the FLONA of Carajás and reinforce the need for management and conservation plans for P. microphyllus in priority areas, where the species finds favorable climatic conditions in future scenarios. In situ and ex situ conservation measures for this species are essential, since extracting the leaves contributes as a source of income for local communities.